Computer aided verification. 30th International Conference, CAV 2018, held as part of the Federated Logic Conference, FloC 2018, Oxford, UK, July 14-17, 2018, Proceedings /: 30th International Conference, CAV 2018, held as part of the Federated Logic Conference, FloC 2018, Oxford, UK, July 14-17, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available